Tren dan Peluang Penelitian Pembelajaran Berbasis Argumentasi Untuk Pemecahan Masalah dalam Pembelajaran Fisika: Analisis Bibliometrik - Ashel, Hazrati; Hamidah, Ida; Anwar, Sjaeful; Muslim, Muslim (JURNAL EKSAKTA PENDIDIKAN (JEP), 2024)
Research on argumentation has been widely conducted and continues to develop. Research trends and opportunities need to be known by researchers to conduct research. To find out this, a bibliometric analysis needs to be conducted. This analysis is conducted to determine the development of publications, trends, and research opportunities on the topic of argumentation in Physics learning. Article data was obtained from Scopus and analyzed using the VOSviewer application. The results obtained are that research in this topic tends to increase every year. Keywords that are trending in this topic include high school, physics and science education, e-learning and dialogic argumentation, and argumentation skills. Meanwhile, keywords that are opportunities are higher education, other fields that study Physics, the use of teaching materials and inquiry, assessment in argumentation-based learning, and understanding concepts. In addition, a relationship between argumentation and problem-solving skills was also obtained. There are still few articles that connected argumentation and problem-solving so that this topic can be an opportunity to conduct research, especially at the university level. We suggest exploring various methods in implementing argumentation in Physics learning. Argumentation can not only improve argumentation skills but also improve various 21st century skills such as problem-solving skills